AMAR MA’RUF NAHI MUNKAR PERSPEKTIF IMAM AL-GHOZALI DALAM PEMBENTUKAN KARAKTER SANTRI PP. DARUSSALAM BLOKAGUNG 2 - Mahmudah Mahmudah; Akbar Hidayatulloh (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2023)
Amar Ma'ruf means a person who invites, calls on or reminds other people or someone of something that is good, true and blessed by Allah SWT. Then nahi munkar means a person who prohibits or prevents all forms of evil or evil that are hated and not blessed by Allah SWT in any way. The aims of this study were (1) to know the concept of Amar Ma'ruf Nahi Munkar from the perspective of Imam Al-Ghozali. (2) Knowing the implementation of Amar Ma'ruf Nahi Munkar according to the perspective of Imam Al-Ghozali in the formation of the character of students at Pondok Pesantren Darussalam Blokagung 2. The research method used is a qualitative approach by collecting data using interviews, observation and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusions. The uniqueness of this study is the dialogue between salafi theory and modern theory, namely the combination of Imam Al-Ghozali's theory and Thomas Lickona's theory. And the results of this study are that the development of the good character of the santri can be seen in terms of their dhohir such as the habits they do and this becomes a parameter of the psychic development of these santri to diagnose heart diseases that infect them. The students become confused about what is absorbed by a science if the administrators pay attention to the criteria of Imam Al-Ghozali. Keywords: Amar Ma'ruf Nahi Munkar, Imam Al-Ghozali, character building.